Transparency in Medicines Regulatory Affairs Reclaiming Missed Opportunities - Y A Vawda; A Gray (South African Journal of Bioethics and Law, 2017)
Transparency is a salutary value in our constitutional architecture. It has also been described as a necessary element in promoting accountability in the regulatory aspects of essential medicines. Despite its several incarnations, the Medicines and Related Substances Act (Medicines Act) retains a provision headed 'Preservation of secrecy' (section 34). This contributionseeks to evaluate section 34 in the context of transparency and ascertain whether it is in conflict with other legislation pertaining to the promotion of access to information and, in particular, whether it is consistent with the Constitution of the Republic of South Africa.